Starch intake and caries increment: A longitudinal study in Finnish adults - Fariah H Jangda; Annaliisa L Suominen; Annamari Lundqvist; Satu Männistö; Ali Golkari; Eduardo Bernabé (Public Health Nutrition)
Abstract